2011
DOI: 10.1074/jbc.m110.176040
|View full text |Cite
|
Sign up to set email alerts
|

JHDM3A Module as an Effector Molecule in Guide-directed Modification of Target Chromatin

Abstract: With the objective of returning cells to their undifferentiated state through alteration of epigenetic states, small molecules have been used that specifically inhibit proteins involved in sustaining the epigenetic system. However, this chemicalbased approach can cause chaotic epigenomic states due to random actions of the inhibitors. We investigated whether JHDM3A/JMJD2A, a trimethylated histone H3-lysine 9 (H3K9me3)-specific demethylase, could function as an effector molecule to selectively demethylate targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Another CTCF histone demethylase partner is KDM4A. The first clue that CTCF could be a KDM4A partner was reported in 2011 by Kang's group, who performed transfection and immunofluorescence assays and observed that the demethylation frequency of KDM4A was enhanced by the presence of CTCF [102]. This study opened the window to another report in 2018, where co-immunoprecipitation was used to demonstrate that CTCF and KDM4A form a protein complex.…”
Section: Ctcf As a Modulator Of Histone Methylationmentioning
confidence: 73%
“…Another CTCF histone demethylase partner is KDM4A. The first clue that CTCF could be a KDM4A partner was reported in 2011 by Kang's group, who performed transfection and immunofluorescence assays and observed that the demethylation frequency of KDM4A was enhanced by the presence of CTCF [102]. This study opened the window to another report in 2018, where co-immunoprecipitation was used to demonstrate that CTCF and KDM4A form a protein complex.…”
Section: Ctcf As a Modulator Of Histone Methylationmentioning
confidence: 73%
“…Given that CTCF plays a major role in the demethylation function of KDM4A [ 8 ], we decided to characterize its expression in our cellular model. By RT-qPCR, we observed that CTCF was overexpressed in the MCF7, MDA-MB-231 and HeLa cell lines when compared to the MCF 10A cells (Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro assays have reported that the presence of CTCF increases the demethylation frequency of KDM4A by up to 80%, suggesting that CTCF has a role in the demethylation function of KDM4A [ 8 ]. Additional support for these datasets was provided by another study that demonstrated that CTCF can interact with the KDM5B histone demethylase and increase its demethylation activity in breast cancer cell lines [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1. The AxioVision intensity profile tool (v4.8) was used (Jeong et al, 2011). IVF, blastocysts from in vitro-fertilization; cSCNT and fSCNT, cumulus cell-and ear-skin fibroblast-derived somatic cell nuclear transfer blastocysts.…”
Section: Generation Of Geps Of Reprogramming-related Genes From Bovinmentioning
confidence: 99%